2011 International Conference on Machine Learning and Cybernetics 2011
DOI: 10.1109/icmlc.2011.6017015
|View full text |Cite
|
Sign up to set email alerts
|

Application of an image processing software tool to crack inspection of crystalline silicon solar cells

Abstract: In this paper, we try to design and integrate an Automatic Optical Inspection System for inspection of polycrystalline silicon solar cells or modules, emphasizing on its image processing, measurement and analysis software utilities. Based on the cell intensity images captured by the electroluminescence imaging technique, we propose an inspecting procedure by using the Windows-based user interface to implement the average gray level tool, the thresholding tool, the positioning tool, the edge detection tool, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Jong-Hann et al [81] developed software and hardware for an automatic optical inspection system to inspect the facial cracks of polycrystalline silicon solar cells or modules. They used the EL imaging technique with a CCD interlaced camera with 768 × 494 pixels resolution with optical lens mounted and illumination unit [81].…”
Section: Electroluminescence Imaging and Photoluminescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Jong-Hann et al [81] developed software and hardware for an automatic optical inspection system to inspect the facial cracks of polycrystalline silicon solar cells or modules. They used the EL imaging technique with a CCD interlaced camera with 768 × 494 pixels resolution with optical lens mounted and illumination unit [81].…”
Section: Electroluminescence Imaging and Photoluminescence Imagingmentioning
confidence: 99%
“…They used the EL imaging technique with a CCD interlaced camera with 768 × 494 pixels resolution with optical lens mounted and illumination unit [81]. The software [81] is based on the use of a Windowsbased user interface to implement the average gray level tool and the binary large object (BLOB) tool. However, it is difficult to distinguish between microcracks and other type of defects like scratches using this approach.…”
Section: Electroluminescence Imaging and Photoluminescence Imagingmentioning
confidence: 99%
“…Breitenstein et al [125] reported that the EL method is superior to the LIT method in terms of cost and quality of the image. The authors of [126,127] have developed software and integrated it with the hardware to develop an automated inspection process for inspecting facial cracks in silicon cells. However, it is difficult to identify between surface cracks and micro-defects using this approach.…”
Section: El Imagingmentioning
confidence: 99%
“…The problem of resolving micro-cracks from these complex luminescence images has been the subject of numerous image processing studies in recent years [4,43,[53][54][55][56][57][58][59][60][61][62][63]. However, in practice, there is very little distinction between micro-cracks and unwanted noise such as cosmetic scratches, dislocation clusters and grain boundaries.…”
Section: Solar Cellmentioning
confidence: 99%